The effect of fibre type and usage ratio on the physical, mechanical and microstructural properties of low molarity ceramic waste powder-based geopolymer composites - Keskin, Asli; Uysal, Mucteba; Akyuncu, Veysel; Avsar, Yunus Emre (TAYLOR & FRANCIS LTD, 2026)
In this study, the effect of fibre type (basalt and polyvinyl alcohol [PVA]) and usage ratio (0.4%, 0.8%, 1.2% by volume) on the physical and mechanical properties of low-molarity geopolymer composites based on blast furnace slag (BFS) and ceramic waste powder (CWP) was investigated. No study has been found in the literature that examines the effect of replacing basalt and PVA fibres with BFS and CWP-based geopolymers on mechanical properties. Unit weight, water absorption, void ratio, ultrasonic pulse velocity, abrasion, toughness, flexural strength, compressive strength (CS), high temperature and freeze-thaw cycles tests were carried out on the specimens to determine the physical and mechanical properties. In addition, microstructural analyses were implemented. As a result, the optimum series has been determined as P4. The CS of PVA-reinforced samples at 300 degrees C is 61%, 42% and 4% higher than that of basalt fibre-reinforced samples with the same ratio. Fibre usage can increase the mechanical properties and abrasion resistance, particularly due to the homogeneous distribution of PVA and its strong bond with the matrix. Additionally, PVA is more effective in reducing porosity/water absorption, enhancing microstructural integrity, delaying microcrack formation, increasing freeze-thaw resistance and may offer advantages in enhancing durability.
Keywords: Environmentally friendly materials; sustainability; ceramic waste powder; geopolymer; physical/mechanical properties; PVA; BLAST-FURNACE SLAG; POLYVINYL-ALCOHOL FIBER; FLY-ASH; HIGH-TEMPERATURE; PVA FIBER; REINFORCED GEOPOLYMER; COMPRESSIVE STRENGTH; POLYPROPYLENE FIBER; ACTIVATED MORTAR; BASALT FIBER; Engineering